(untitled) - Ahrons, Constance R (New York, 1994)
Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Divorce -- United States -- Longitudinal studies; Ly hôn -- Hoa Kỳ -- Nghiên cứu theo dõi